The Revelation of John - Barclay, William; (1907-1978) (Scotland, 1961)
Revelation is stylistically unlike any other part of the New Testament and is notoriously bewildering and difficult to understand. William Barclay carefully explores its themes in ways that lead us to the revelation that Christians shall know heaven and the true glory of God.
Keywords: Bible -- Revelation -- Commentaries